High-resolution Genetic and Physical Map of the Lgn1 Interval in C57BL/6J Implicates Naip2 or Naip5 in Legionella pneumophila Pathogenesis - Growney, Joseph D.; Dietrich, William F.

(untitled) (Genome Research, 2000)
Prior genetic and physical mapping has shown that theNaip gene cluster on mouse chromosome 13D1-D3 contains a gene, Lgn1, that is responsible for determining the permissivity of ex vivo macrophages to Legionella pneumophila replication. We have identified differences in the structure of the Naip array among commonly used inbred mouse strains, although these gross structural differences do not correlate with differences in L. pneumophilapermissiveness. A physical map of the region employing clones of the C57BL/6J haplotype confirms that there are fewer copies ofNaip in this strain than are in the physical map of the 129 haplotype. We have also refined the genetic location ofLgn1, leaving only Naip2 and Naip5as candidates for Lgn1. Our genetic map suggests the presence of two hotspots of recombination within the Naiparray, indicating that the 3′ portion of Naip may be involved in the genomic instability at this locus.[The sequence data described in this paper have been submitted to the GenBank data library under accession nos. AF240489–AF240530.]